2023
DOI: 10.26434/chemrxiv-2023-m0r2f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamics of Li+–Crown Ether Interactions in Aqueous Solvent

Abstract: Lithium ion-based batteries are ubiquitous in modern technology due to applications in personal electronics and high-capacity storage for electric vehicles. Concerns about lithium supply and battery waste have prompted interest in lithium recycling methods. The crown ether, 12-crown-4, has been studied for its abilities to form stable complexes with lithium ions (\ce{Li+}). In this paper, molecular dynamics simulations are applied to examine the binding properties of a 12-crown-4—\ce{Li+} system in aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The selectivity of crown ethers is driven by the size of the cation relative to the crown ether cavity and the strength of the interaction is related to the decrease in free energy associated with forming the complex. 27,28 It was found that stronger interactions led to increased partitioning and lower salt diffusivities. 29 Interestingly, strong interactions can lead to selective separations through partition driven gating; here, molecules with greater partition coefficients preferentially enter a confined pore thereby preventing other molecules from entering and subsequently diffusing through the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of crown ethers is driven by the size of the cation relative to the crown ether cavity and the strength of the interaction is related to the decrease in free energy associated with forming the complex. 27,28 It was found that stronger interactions led to increased partitioning and lower salt diffusivities. 29 Interestingly, strong interactions can lead to selective separations through partition driven gating; here, molecules with greater partition coefficients preferentially enter a confined pore thereby preventing other molecules from entering and subsequently diffusing through the membrane.…”
Section: Introductionmentioning
confidence: 99%